Morphometric Study of Suprascapular Notch in Indian Dry - Venkateswara Rao, Madala; Hema, Lattupalli (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The suprascapular notch is a semicircular notch at the superiorborder of scapula, just medial to the base of the Coracoid process, is bridged bythe superior transverse scapular ligament, which is sometimes ossified and theforamen which is thus completed, transmits the suprascapular nerve to thesupraspinatus fossa. Variations in the morphology of suprascapular notch havebeen identified as one of the causes of suprascapular nerve entrapment.